If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 2(3x + 8) + 17 = 4x + 21 Reorder the terms: 5x + 2(8 + 3x) + 17 = 4x + 21 5x + (8 * 2 + 3x * 2) + 17 = 4x + 21 5x + (16 + 6x) + 17 = 4x + 21 Reorder the terms: 16 + 17 + 5x + 6x = 4x + 21 Combine like terms: 16 + 17 = 33 33 + 5x + 6x = 4x + 21 Combine like terms: 5x + 6x = 11x 33 + 11x = 4x + 21 Reorder the terms: 33 + 11x = 21 + 4x Solving 33 + 11x = 21 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 33 + 11x + -4x = 21 + 4x + -4x Combine like terms: 11x + -4x = 7x 33 + 7x = 21 + 4x + -4x Combine like terms: 4x + -4x = 0 33 + 7x = 21 + 0 33 + 7x = 21 Add '-33' to each side of the equation. 33 + -33 + 7x = 21 + -33 Combine like terms: 33 + -33 = 0 0 + 7x = 21 + -33 7x = 21 + -33 Combine like terms: 21 + -33 = -12 7x = -12 Divide each side by '7'. x = -1.714285714 Simplifying x = -1.714285714
| 5-3(x-7)=2(2-x) | | 2m^3(4m^2)= | | 4(x^3-6x^2+9)=0 | | 500=30f+100 | | x=9x-22 | | X+2x-4x=41 | | -65-12x=65-7x | | 2w^2+9w+0=0 | | 7n-4(-3n+4)= | | P(p+3)=2(p+3) | | 6x-6-3x=5x+10 | | 7(x-6)=79 | | 0.5T+4.1=5.7-0.3 | | 23-6x=41 | | x-16+(-24)=7 | | 5z=-3(x+7) | | 1.2m-12cm= | | 6a+1=27 | | 35=5x+6-10 | | 8x-(8+6x)=-16 | | -46-2x=-7x+104 | | 3[2x-2-x]=5x+10 | | 3x-5=48+40x | | -10w+9=-6 | | e+25-32=8 | | 6.5n=110.5 | | Y-10.8=45 | | 3x-5=-48+40x | | 5y+2=5y+4 | | 2e+7-4e=15 | | n-20.39=-3.39 | | 3[2(x+1)-x]=5(x+2) |